Optimal administration time of vitamin C after 131I therapy in differentiated thyroid cancer based on propensity score matching - Liu, Ye; Wang, Yuhua; Zhang, Wanchun (Frontiers in Surgery, 2022)
Objectives: This study aimed to investigate the protection of the salivary glands by vitamin C administration at 2 and 24 h after an initial treatment using iodine-131 (131I) in patients with differentiated thyroid cancer (DTC) and examined the optimal administration time of vitamin C to protect the salivary glands from radiation injury. Method: The clinical data of patients with differentiated thyroid carcinoma who had been treated with 131I in the Department of Nuclear Medicine in Shanxi Bethune Hospital from January 2014 to December 2020 were retrospectively analyzed. The propensity score matching method was adopted to match patients who received the administration of vitamin C at 2 h with those receiving administration at 24 h. A total of 230 pairs/460 patients were enrolled in the study. The chi-squared (χ²) or Fisher's exact test was used to compare the indicators representing the incidence of salivary gland injury between the two groups. Results: The incidence of salivary gland injury (17.39%) with acidic substances at 2 h was lower compared with administration at 24 h (26.96%). The incidence of acute salivary gland injury (15.22%) and chronic salivary gland injury (26.09%) in the 24-h group were higher than those in the 2-h group (4.78% and 18.26%, respectively). The differences in the left submandibular gland concentrate index and right submandibular gland concentrate index were statistically significant before and after treatment in both the 2 and the 24-h groups; these functions had been impaired after treatment. Conclusions: Following treatment with 131I, the protective effect of acidic substances administered at 2 and 24 h on the salivary glands were different. The incidence of salivary gland injury in the 2 h acid stimulation group was lower than in the 24 h acid stimulation group. The present study revealed that 131I treatment did cause some injury to the salivary glands and that the protective effect of administering vitamin C at 2 and 24 h may be limited. Accordingly, protection against salivary gland injury should be conducted using comprehensive measures.